The research into the influence of ecological petrol additives in the automobile laboratory - Butkus, Algis; Pukalskas, Saugirdas (Transport, 2004)
Looking forward to Lithuania becoming a member of the EU it is very important to use a larger amount of renewing fuel. Based on economic and environmental considerations in Lithuania, we are interested in studying the effects of ethanol contents in the blended ethanol‐petrol fuel on the engine performance and pollutant emission of SI engine. Therefore, we used engine test facilities to investigate the effects on the engine performance and pollutant emission of 3,5% and 7,0% ethanol in the fuel blend and special additives, which reduce emissions and increase octane rating. The tests were carried out in the laboratory on a chassis dynamometer with two different cars. The experiment results showed that ethanol used in a fuel blend with petrol had a positive influence on engine performance and exhaust emission. First Published Online: 27 Oct 2010